2020
DOI: 10.1097/gme.0000000000001711
|View full text |Cite
|
Sign up to set email alerts
|

Inverse association between dietary fiber intake and depression in premenopausal women: a nationwide population-based survey

Abstract: Objective: Depression is among the most common neuropsychiatric disorders, and its prevalence is twofold higher in women than in men. This study aimed to investigate the relationship between dietary fiber intake and depression in women by menopause status using data from a nationwide population-based survey conducted in Korea. Methods: We utilized the Korea National Health and Nutritional Examination Survey data for 2014, 2016, and 2018 with a complex s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…In our study, we found a negative association between dietary fiber intake and depressive symptoms, which is consistent with the results of previous studies ( Woo et al, 2006 ; Gangwisch et al, 2015 ; Kim et al, 2015 , 2020 ; Khayyatzadeh et al, 2021 ; Liu et al, 2021 ; Chrzastek et al, 2022 ). The Women’s Health Initiative Observational Study ( Gangwisch et al, 2015 ) showed that among postmenopausal women, higher dietary fiber consumption was associated with a decrease in OR for depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, we found a negative association between dietary fiber intake and depressive symptoms, which is consistent with the results of previous studies ( Woo et al, 2006 ; Gangwisch et al, 2015 ; Kim et al, 2015 , 2020 ; Khayyatzadeh et al, 2021 ; Liu et al, 2021 ; Chrzastek et al, 2022 ). The Women’s Health Initiative Observational Study ( Gangwisch et al, 2015 ) showed that among postmenopausal women, higher dietary fiber consumption was associated with a decrease in OR for depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…Dietary fiber is a kind of plant cell wall that is resistant to human enzyme digestion but may be digested by gut microbial enzymes into short-chain fatty acids (SCFA) ( Smith and Wilds, 2009 ; Taylor and Holscher, 2020 ). Higher dietary fiber intake has been shown to be a protective factor for depressive symptoms in different study populations ( Kim et al, 2020 ; Khayyatzadeh et al, 2021 ; Liu et al, 2021 ; Chrzastek et al, 2022 ). Also, dietary fiber intake may reduce the risk of newly diagnosed diabetes ( Stevens et al, 2002 ; Yao et al, 2014 ; Jin et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the benefits of fiber consumption against perinatal depression were increasingly evident in obese rats, whose fiber-enriched diets significantly attenuated cognitive effects and maternal depression (Liu et al, 2020). In addition, an increased dietary fiber intake has been associated with reduced depression in premenopausal, but not in postmenopausal women (Kim et al, 2021).…”
Section: Fibermentioning
confidence: 99%
“…Importantly, these changes may be associated with a reduction in depressive symptoms [ 109 ]. Some previous studies have found that 1 g of fiber per 1000 kcal is sufficient to observe the protective actions of fiber against depression in premenopausal but not postmenopausal women [ 110 ]. Further studies are warranted to determine the quantity of fiber intake to show its preventive actions against depression.…”
Section: Translational Opportunities: Clinical Management Of Mdd Thro...mentioning
confidence: 99%